Defects in coding joint formation in vivo in developing ATM-deficient B and T lymphocytes - Huang, Ching-Yu (The Rockefeller University Press, 2007)
Ataxia-telangiectasia mutated (ATM)–deficient lymphocytes exhibit defects in coding joint formation during V(D)J recombination in vitro. Similar defects in vivo should affect both T and B cell development, yet the lymphoid phenotypes of ATM deficiency are more pronounced in the T cell compartment. In this regard, ATM-deficient mice exhibit a preferential T lymphopenia and have an increased incidence of nontransformed and transformed T cells with T cell receptor α/δ locus translocations. We demonstrate that there is an increase in the accumulation of unrepaired coding ends during different steps of antigen receptor gene assembly at both the immunoglobulin and T cell receptor loci in developing ATM-deficient B and T lymphocytes. Furthermore, we show that the frequency of ATM-deficient αβ T cells with translocations involving the T cell receptor α/δ locus is directly related to the number of T cell receptor α rearrangements that these cells can make during development. Collectively, these findings demonstrate that ATM deficiency leads to broad defects in coding joint formation in developing B and T lymphocytes in vivo, and they provide a potential molecular explanation as to why the developmental impact of these defects could be more pronounced in the T cell compartment.